AN ANALYSIS OF READING COMPREHENSION EXPERIENCES BETWEEN MALE AND FEMALE STUDENTS AT SMAN 20 GOWA - Rina Bakri (Jurnal Riset Guru Indonesia, 2026)
Reading comprehension is an essential skill in English language learning because it helps students understand and interpret written texts effectively. This study aimed to explore the reading comprehension experiences of male and female students at SMAN 20 Gowa using a qualitative descriptive approach. The participants consisted of 37 students, including 18 male students and 19 female students. Data were collected through classroom observations, interviews, questionnaires, and document analysis. The findings revealed that female students demonstrated stronger motivation, more active classroom participation, and more effective reading strategies than male students. Female students also showed greater confidence during discussions and more frequent reading habits outside the classroom. In contrast, male students tended to experience difficulties in understanding long texts and unfamiliar vocabulary, resulting in lower classroom participation and reading engagement. The study also found that vocabulary mastery, learning environment, classroom interaction, and reading motivation significantly influenced students’ reading comprehension experiences. These findings suggest that English teachers should apply interactive and gender-responsive teaching strategies to improve students’ reading comprehension learning. This study contributes to understanding gender differences in reading comprehension experiences within Indonesian senior high school contexts.